Analisis Persepsi Mahasiswa Universitas Jember terhadap Isu Palestina: Faktor-Faktor yang Mempengaruhi Solidaritas - Kusuma, Anas Pramesti; Susanto, Tantut; Maulida, Firdina; Putri, Cindy Destia; Bimantoro, Aditya Sindhu Langit; Nuraini, Muvida Putri; Manurung, Martha; Rabbani, Mohamad Iqbal Fahmi; Dennata, Maxzellent Fullevind Surya; Soko, Febry Lambang Killy Aji (UNIVERSITAS SERAMBI MEKKAH, 2025)
The Palestine-Israel conflict is a global issue that attracts attention, including in Indonesia, and touches social, political, religious, and humanitarian aspects. Solidarity with Palestine in Indonesia is in line with the mandate of the 1945 Constitution which supports the independence of other nations and opposes colonialism. The conflict that has roots in the late 19th century, exacerbated by the Balfour Declaration and subsequent wars, has led to human rights violations and humanitarian crises. Students are expected not only to follow the development of issues through social media, but also to be able to filter information critically. This study aims to analyze the perceptions of Jember University students towards the Palestinian conflict and the factors that influence their solidarity, as well as to examine the internalization of the concept of state defense in the form of solidarity with international humanitarian issues. This research uses a mixed methods approach, combining quantitative methods through the distribution of questionnaires and qualitative methods through in-depth interviews with active students of the University of Jember.